Comparative effectiveness of wild bee pollination on the post-harvest characteristics of Grewia asiatica (Malvaceae) - Akram, Waseem; Sajjad, Asif; Ali, Mudssar; Ahmad, Ammad; Ali, Intazar; Saddiq, Bushra; Yasin, Muhammad; Anjum Aqueel, Muhammad (Journal of Asia-Pacific entomology, 2022)
[Display omitted] •Among bees, Apis dorsata was the most abundant floral visitor of Grewia asiatica.•Visitation frequency and stay time were higher in A. dorsata.•Visitation rate, pollen load and pollen deposition were higher in Megachile bicolor.•The maximum fruit weight was recorded for M. bicolor with more shelf life. Measuring the pollination potential of different native bees is helpful in identifying the most efficient species for their conservation and proper utilization. The current study was carried out at the Research Farm of The Islamia University of Bahawalpur to compare the pollination efficiency of four native bee species: Apis dorsata, Megachile bicolor, M. cephalotes and Megachile (Callomegachile) sp. Apis dorsata was the most abundant floral visitor of Grewia asiatica comprising 36.46% of floral visitors following by M. cephalotes and Megachile sp. The peak abundance of A. dorsata and M. bicolor was recorded at 12:00 and 08:00, respectively whereas for M. cephalotes and Megachile sp. at 16:00. Visitation frequency, stay time, body and proboscis length were significantly higher in A. dorsata whereas visitation rate, pollen load and pollen deposition were significantly higher in M. bicolor. The maximum fruit weight was recorded when M. bicolor and Megachile sp. had been the pollinators. The post-harvest fruit weight loss was lower in M. bicolor pollinated fruit -with more gradual wrinkling- than in fruit that had resulted from pollination by A. dorsata, M. cephalotes and Megachile sp. Our results suggest that M. bicolor was better pollinator of G. asiatica in terms of its reproductive success and post-harvest qualities. Further studies should focus on conservation of M. bicolor in the region.